The Influence of Financial Literacy, Financial Inclusion, and Fintech Usage on MSME Financial Performance: Study on MSME Actors of the Batik Handicraft Industry Center in Solo Raya - Lady Noor Majid; Imronudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
MSMEs are the main pillar of the Indonesian economy, playing a major role in employment, increasing GDP, and exporting local products. The government targets 90% financial inclusion by 2024, but low financial literacy is a challenge. MSMEs' performance could be improved by using fintech, however optimizing economic impact and guaranteeing business sustainability require a strong grasp of finance. With an emphasis on the connection between these factors and MSME performance, this study attempts to investigate how financial inclusion, financial literacy, and financial technology use affect MSMEs' financial success. The research involved 160 MSME owners from the Solo Besar Batik Craft Center, all of whom have adopted fintech-based payment systems. A straightforward random sampling procedure was used to choose the sample. Using a Likert scale, a questionnaire was used to gather primary data. Data analysis was conducted using SmartPLS 3 software, applying the probability sampling method (simple random sampling). The findings revealed that financial literacy, financial inclusion, and the use of financial technology significantly and positively influence the financial performance of MSMEs. Financial literacy aids in better management and increased profitability, financial inclusion broadens access to financial services, and financial technology enhances access to capital and improves transaction management. This research confirms the importance of these three factors for the growth and sustainability of MSMEs.